Perceived Self-Regulation and Violence Tendency: Psychological Implications in Turkey - Tekke, Mustafa; Barut, Ya?ar (Letiges, 2024)
This study aims to investigate the relationship between perceived self-regulation life satisfaction and violence tendencies. This study uses a quantitative approach. The sample in this study consisted of 340 participants from the entire class population. Data was collected using a questionnaire book guided by a Likert scale of 1 to 5. Data analysis was carried out in several stages, namely self-regulation scale analysis, tendency scale analysis and life scale analysis. These findings indicate a positive correlation between perceived self-regulation and life satisfaction, as well as a negative relationship between perceived self-regulation and violent tendencies. The predictive role of perceived self-regulation on life satisfaction is apparent, although the relationship between violent tendencies and life satisfaction remains ambiguous. This research shows that perceived self-regulation plays an essential role in an individual's well-being and that good self-regulation has a lower likelihood of violence.